2006
DOI: 10.1007/s10384-005-0296-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c-Jun and Bcl-2 Family Proteins in Apoptotic Photoreceptors of RCS Rats

Abstract: c-Jun and Bax may play a role in photoreceptor apoptosis in RCS rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Apoptosis can be inhibited by the inhibition of the expression of the apoptosis-associated genes, including Bax, or by the overexpression of Bcl-2 (38,39). Previous studies have demonstrated that Bax is upregulated in photoreceptors and Bcl-2 was not downregulated in RCS rat retinas on day 28 compared with day 21 (40). The role of the Bcl-2 family in the apoptotic process of photoreceptors remains to be elucidated (41).…”
Section: Discussionmentioning
confidence: 93%
“…Apoptosis can be inhibited by the inhibition of the expression of the apoptosis-associated genes, including Bax, or by the overexpression of Bcl-2 (38,39). Previous studies have demonstrated that Bax is upregulated in photoreceptors and Bcl-2 was not downregulated in RCS rat retinas on day 28 compared with day 21 (40). The role of the Bcl-2 family in the apoptotic process of photoreceptors remains to be elucidated (41).…”
Section: Discussionmentioning
confidence: 93%
“…In RCS rats, disabled photoreceptor outer segment phagocytosis drives the apoptotic photoreceptor cell death (Tso et al, 1994). Increased expression of c-Jun and BAX proteins has been reported during the course of this process (Katai et al, 2006), which points to mitochondrial involvement and the activation of caspases (Perche et al, 2008), although it seems that the apoptotic process is not mediated by Bcl-2 (Katai et al, 2006;Sharma, 2001).…”
Section: Activation Of Apoptotic Pathways: Role Of the Mitochondriamentioning
confidence: 97%
“…It has been suggested that subsequent chronic accumulation of the non-phagocytosed photoreceptor outer segment debris may induce the photoreceptor degeneration [13][14][15]. As a consequence, photoreceptors die by showing morphological signs of apoptosis [16][17][18][19][20][21]. Then, retinal remodelling seems to occur after decline of photoreceptor numbers [22].…”
Section: Introductionmentioning
confidence: 98%